The Influence of Social Media Communication Towards Customer-Based Brand Equity on Netflix - Eka Putri, Laila Febriyuni; Rufaidah, Popy (International Research Journal of Business Studies, 2024)
This study aims to analyze how social media communication seen from user-generated content, firm-generated content, and distribution intensity affects customer-based brand equity on Netflix. Respondents in the study were 321 Netflix subscribers. This study uses a lower-order construct as a research model. Based on the results of research that has been conducted, show that firm-generated content (FGC), user-generated content (UGC), and distribution intensity (DI) affect customer-based brand equity (CBBE) at different levels. Although UGC has a smaller effect size compared to FGC, it still has significant relevance. Distribution intensity is important for increasing brand awareness and loyalty, although it has no direct impact on perceived quality. This in-depth understanding can guide marketing and brand management decisions to effectively utilize these components.